2014
DOI: 10.1175/mwr-d-13-00137.1
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Tibetan Plateau Vortices by 10–30-Day Intraseasonal Oscillation*

Abstract: Tibetan Plateau (TP) vortices and the related 10-30-day intraseasonal oscillation in May-September 1998 are analyzed using the twice-daily 500-hPa synoptic weather maps, multiple reanalysis datasets, and satelliteretrieved brightness temperature. During the analysis period, distinctively active and suppressed periods of TP vortices genesis are noticed. In 1998, nine active periods of TP vortices occurred, which were largely clustered by the cyclonic circulations associated with the intraseasonal oscillation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
(47 reference statements)
3
38
0
Order By: Relevance
“…Then the active and break composites of filtered circulation, precipitation, moisture conditions, and diabatic heating are constructed in Fig. Zhang et al (2014) showed similar circulation and moisture conditions by analyzing TP vortices and the related 10-30-day intraseasonal oscillation. When the QBWO signal is active, more precipitation occurs in the CETP and its downstream area, while less occurs in northern India, northern China, and eastern China.…”
Section: The Relationship Between Qbwo and The Onset And Active/breakmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the active and break composites of filtered circulation, precipitation, moisture conditions, and diabatic heating are constructed in Fig. Zhang et al (2014) showed similar circulation and moisture conditions by analyzing TP vortices and the related 10-30-day intraseasonal oscillation. When the QBWO signal is active, more precipitation occurs in the CETP and its downstream area, while less occurs in northern India, northern China, and eastern China.…”
Section: The Relationship Between Qbwo and The Onset And Active/breakmentioning
confidence: 99%
“…He et al (2006) found that, in summer, the southeastern TP was the most active ISV area of blackbody temperature. In particular, the ISV modes over the TP, to some extent, can influence local and even large-scale weather systems, including the plateau low vortex (Zhang et al 2014), subtropical high (Li et al 1991), and South Asian high (Liu and Lin 1991), as well as the precipitation anomaly in eastern China (Zhou et al 2000). ISV signals over the TP may originate from either the lower latitudes, such as the Bay of Bengal and the southern rim of the TP (Krishnamurti and Subrahmanyam 1982;Zhang et al 2009) or middle-to-high latitudes (Blackmon et al 1984a,b;Xie et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…For the former aspect, the location of the SAH center usually varies in the east-west direction, known as ''bimodality'': the Tibetan type (or eastern pattern) is when the center is located at the southern slope of the TP and the Iranian type (or western pattern) is when the center is located at the Plateau of Iran (IP). These two SAH types are associated with apparently different circulation at multiple time scales ranging from a few days to submonthly and interannual scales (Krishnamurti 1973;Liu et al 2007;Luo et al 1982;Wei et al 2014;Zhang et al 2014;Zhang et al 2002), which has been linked to extreme weather and climate events in Asia (Ye and Gao 1979). For the latter aspect, the SAH intensity is also linked to summer extreme climate events and rainfall anomalies over Asia and over western Africa, the North Pacific, and Central America, especially at interannual scales (Kanamitsu and Krishnamurti 1978;Zhang et al 2005;Zhao et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This study used multiple available reanalysis datasets (Table 1) to derive these variables in order to reduce the potential uncertainties introduced by the choice of reanalysis datasets, and thus ensure the robustness of the analysis results. A reanalysis ensemble method was applied, and the ensemble circulation fields were treated as an approximation of observed atmospheric circulation (Li et al 2013b;Zhang et al 2014). These variables simulated by the WRF were compared with the reanalysis ensemble to understand the causes of the precipitation bias in the WRF simulation.…”
Section: Observed Precipitation and Atmospheric Circulation From Multmentioning
confidence: 99%